Assessment of the efficacy and safety of neuroendoscopic procedures for intracranial pathologies: A single-centre retrospective study with 318 intracranial endoscopic procedures - Mohammed Issa; Clara Dannehl; Carmen J. Büsken; Nieke Ueding; Angelika Seitz; Sandro M. Krieg; Andreas W. Unterberg; Ahmed El Damaty (Brain and Spine)
Introduction: Neuroendoscopy has become a well-established procedure for treating various intracranial conditions. Research question: We evaluated the advantages of that technique, with focus on adverse events. Material and methods: Retrospective analysis included all patients who underwent neuroendoscopic procedures between January 2017 and December 2023. We conducted comparative analysis considering factors such as age, gender, follow-up duration, etiology, preoperative symptoms, clinical and radiological benefits, as well as surgical and nonsurgical adverse events rates. Results: Total of 318 neuroendoscopic procedures within 257 surgeries in 225 patients were included, with mean age of 18.8 ± 21.4 years. 170 cases (66.1%) were pediatric versus 87 cases adults (33.9%). Most common aetiologies were peri- and intraventricular cysts (27.2%), idiopathic aqueduct stenosis (24.9%), tumours (23.7%), and post-haemorrhagic hydrocephalus (17.1%). Procedures included endoscopic third ventriculostomy (51.0%), cyst fenestration (21.0%), and endoscopic-assisted ventricular catheter placements (19.5%). Headache was predominant preoperative symptom (42.0%). During follow-up, 84.8% and 82.5% of cases showed clinical and radiological improvement, respectively. Early surgical adverse events were observed in 5.4% of cases, while non-surgical adverse events occurred in 3.1%. There was no significant difference in the surgical adverse events rate between children and adults (4.7% vs. 6.9%, p = 0.563), compared to significant higher non-surgical adverse events in adults (6.9% vs 1.2%, p=0.020). Discussion and conclusion: Neuroendoscopy has demonstrated effectiveness and safety in treating intracranial diseases, boasting a low adverse events rate. Our study found no significant difference in the surgical adverse events rates between pediatric and adult groups.